Variation of Mixed Banana peel Substrate and Cow Dung in Biogas Pressure as a Learning Source for Renewable Energy Sources - Puspitawati Puspitawati; Riswanto Riswanto; Nyoto Suseno (Indonesian Review of Physics (IRiP), 2022)
The supply of world energy resources is increasingly depleted. The abundance of cow manure and banana peel can cause environmental pollution. It can be used as raw material for biogas because both materials have a high methane gas ratio. This research is an experiment with six variations in the amount of mixture in each experiment. Results of the research on gas pressure and the best biogas production results using 1-litre banana peel substrate and 4-litre cow dung. Data shows that the gas pressure is faster and is greater when the pH of the mixture is acidic 6.2, the mixture is thick green and has a strong odour. Gas pressure on day 20 is obtained by 106421 Pascal. The average value of the results of the validation of the learning resources of the three aspects of an assessment is 82.3%; it shows that the poster can be used as a learning resource.